2019
DOI: 10.3390/ijgi8120536
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR and UAV System Data to Analyse Recent Morphological Changes of a Small Drainage Basin

Abstract: In this paper, the preliminary results of an integrated geomorphological study carried out in a 1.6 ha catchment area located on the eastern side of the Crati River valley (northern Calabria, South Italy) have been presented. An orthophoto and shaded relief map of the study catchment, obtained by 288 unmanned aerial vehicle (UAV) images, integrated with field geomorphological surveys have been used to produce a detailed map of landslides and water erosion phenomena. The study area is characterized by active mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The mass balance shows a deficit of 0.69 × 10 6 m 3 (about 44% volume loss). Negative mass balances were generally attributed to the removal of material by surface runoff or river erosion, or, in some case, is the result of DTM errors [38,88,89]. In our case, the multi-temporal analysis and field observations showed that part of the mobilized material reached the Straface River and was eroded by the water flow, which has also limited the development of the accumulation area.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The mass balance shows a deficit of 0.69 × 10 6 m 3 (about 44% volume loss). Negative mass balances were generally attributed to the removal of material by surface runoff or river erosion, or, in some case, is the result of DTM errors [38,88,89]. In our case, the multi-temporal analysis and field observations showed that part of the mobilized material reached the Straface River and was eroded by the water flow, which has also limited the development of the accumulation area.…”
Section: Discussionmentioning
confidence: 54%
“…In the last few years, among the remote sensing techniques, there has been a rapid development of the application of Unmanned Aerial Vehicles (UAV) for landslide studies [36][37][38][39][40]. The advantages of UAV-based remote sensing are the following [41]: (i) realtime applicability; (ii) flexible survey planning; (iii) high resolution and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results highlight that the SLs significantly control the present-day morphodynamic of the landscape (Figure 5b), and consequently are a great source of sediment delivered to streams (Roda-Boluda et al 2018;Borrelli et al 2019;Zhu et al 2019;Conforti et al 2021). Along the slopes, the occurrence of SLs was observed either isolated or clustered in groups of several landslides.…”
Section: Shallow Landslides and Their Relation With Geo-environmental Variablesmentioning
confidence: 82%
“…In recent years, the rapid development of low-altitude remote sensing platforms such as UAV has provided a new method of data acquisition for SfM photogrammetry. Because of its low cost, high data acquisition efficiency, and simple and flexible methods, this method has been applied to many fields of geoscience research [42,43]. As UAV flying heights are close to the ground, the accuracy of the obtained data is also improved, which can increase the terrain details and provide a new method for describing the tectonic active landscape [38,44].…”
Section: Methodology and Datamentioning
confidence: 99%